The Role of Blockchain in Career Development Strategy Innovation in Modern Organizations - Melianto, Donny; Kurnadi, Kurnadi; Ulumiddin, Ulumiddin; Halik, Abdul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The aim of this research is to identify the potential of blockchain technology in overcoming problems that exist in traditional career development systems and provide insight into how organizations can use this technology to create more effective career development strategies. Blockchain offers significant potential to revolutionize career development strategies in modern organizations, by providing solutions to problems such as lack of transparency, data security and process inefficiencies[1]. This technology can be used to verify credentials, track training, manage performance, and provide personalized recommendations. Blockchain implementation requires a deep understanding of challenges and opportunities, as well as strategies to overcome issues such as scalability, costs, and regulations (Nabi, 2024). Organizations need to conduct careful cost-benefit analysis and partner with blockchain service providers to succeed